Razlogi za študij medicine in dentalne medicine pri študentih prvega letnika Medicinske fakultete v Ljubljani - Omejec, Janja (Zdravniški vestnik, 2017)
Background: In addition to clinical knowledge, communication skills and sovereign decision making, a good doctor is also expected to posses professional values, including the ability to establish empathic relationships with patients. The purpose of the study was to identify the reasons that lead students to choose the study of dental medicine/medicine, and determine the level of emphaty in relation to the choice of study in the first year students of the Faculty of Medicine in Ljubljana. Methods: For the needs of the research we developed a questionnaire, which included basic data on students, their reasons for choosing the study of medicine or dental medicine and the Jefferson scale of empathy-version for students (JSE-S version with a modified scale with 16 arguments). The questionnaire was forwarded to all 227 first-year students in the academic year 2014/15 at the completion of the Communication course. Results: The study involved a total of 216 (response 95.2 %) students; 158 medical students and 58 students of dental medicine. Among the reasons for enrollment to the Medical Faculty, the highest proportion of medical students indicated a desire to help people (85.3 %), a desire to improve human health (78.8 %) and a desire to work with people (64.7 %); 28.8 % of the medical students chose the argument "because employment is guarantee", while 14.1 % of medical students believed the argument "because it is well paid" was the reason to choose the study of medicine. The students of dental medicine most often choose the following answers: a desire to help people (87.9 %), a desire to improve human health (74.1 %), followed by a desire to work with people (65.5 %). The argument "because employment is guaranteed" convinced 50 % of the students, and the argument "because the pay is good" convinced 46.6 %. Three claims were significantly associated with self-assessment of empathic stance: the arguments "because I want to help people" (91.08 +- 10.65 vs. 86.61 +- 12.56; p = 0.037) and "because I want to work with people" (91.82 +- 10.18 vs. 87.90 +- 12.11; p = 0.012) were associated with a greater self-assessmentwhile the argument "because the pay is good" (91.36 +- 11.41 vs. 87.29 +- 9.01; p = 0.023) was associated with a lower self-assessment of empathic stance. Conclusion: Students who want to help people have higher level of self-assessment of empathic stance. The task of a medical faculty is to ensure that students whose choice of study is based on their humanist values are encouraged to have those values further developed and put into practice during their study.
Keywords: dental medicine; dentalna medicina; medical students; study; študenti medicine; študij